Peran Komitmen dan Psychological Empowerment dalam Meningkatkan Kinerja Pendamping PKH di Kabupaten Kolaka - Ardiansa, Windra; Kumalasari, Fitri; Ismanto, Ismanto (University of Riau Kepulauan, 2025)
This research explores the effect of commitment and psychological empowerment on the performance of Family Hope Program (PKH) companions in Kolaka Regency. Utilizing a quantitative explanatory approach, data were gathered through a literature review and questionnaires. The study encompassed all PKH assistants in Kolaka, with a total of 34 respondents selected through a census sampling method. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) via SmartPLS 3. The results reveal that both commitment and psychological empowerment significantly and positively influence performance